The effects of β-hydroxy-β-methylbutyrate or HMB-rich nutritional supplements on sarcopenia patients: a systematic review and meta-analysis - Su, Hai; Zhou, Haojing; Gong, Yichen; Xiang, Sicheng; Shao, Weijie; Zhao, Xinzheng; Ling, Hao; Chen, Guoqian; Tong, Peijian; Li, Ju (Frontiers in Medicine, 2024)
Background Sarcopenia is a progressive, systemic skeletal muscle disorder. Resistance exercise and physical activity have been proven effective in its treatment, but consensus on pharmacological interventions has not yet been reached in clinical practice. β-Hydroxy-β-methylbutyrate (HMB) is a nutritional supplement that has demonstrated favorable effects on muscle protein turnover, potentially contributing to beneficial impacts on sarcopenia. Aim To assess the potential positive effects of HMB or HMB-containing supplements on individuals with sarcopenia, a systematic review and meta-analysis was conducted. Methods A systematic review and meta-analysis were conducted on randomized controlled trials (RCTs) examining the treatment of sarcopenia with HMB. Two assessors independently conducted screening, data extraction, and bias risk assessment. Outcome data were synthesized through a random-effects model in meta-analysis, using the mean difference (MD) as the effect measure. Results A meta-analysis was conducted on six studies. HMB or HMB-rich nutritional supplements showed a statistically significant difference in Hand Grip Strength (HGS) for sarcopenia patients [MD = 1.26, 95%CI (0.41, 2.21), p = 0.004], while there was no statistically significant difference in Gait Speed (GS) [MD = 0.04, 95%CI (−0.01, 0.08), p = 0.09], Fat Mass (FM) [MD = −0.18, 95%CI (−0.38, 0.01), p = 0.07], Fat-Free Mass (FFM) [MD = 0.09, 95%CI (−0.23, 0.42), p = 0.58], and Skeletal Muscle Index (SMI) [MD = 0.01, 95%CI (−0.00, 0.01), p = 0.13]. Conclusion HMB or HMB-rich nutritional supplements are beneficial for muscle strength in sarcopenia patients. However, there is limited evidence demonstrating significant effects on both muscle strength and physical performance in sarcopenia individuals. HMB may be considered as a treatment option for sarcopenia patients. Systematic review registration CRD42024512119.